2021
DOI: 10.1007/s10668-020-01194-y
|View full text |Cite
|
Sign up to set email alerts
|

Introducing urine-enriched biochar-based fertilizer for vegetable production: acceptability and results from rural Bangladesh

Abstract: Improved agricultural practices that increase yields and preserve soils are critical to addressing food insecurity and undernutrition among smallholder farmer families. Urine-enriched biochar has been shown to be an accessible and effective fertilization option in various subtropical countries; however, it is new to Bangladesh. To better understand attitudes and experiences preparing and using urine-enriched biochar fertilizer, mixed-methods research was undertaken among smallholder farmers in northeastern Ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…(2017) and Sutradhar et al. (2021): average YI of 50%–100% within a large number of practitioner field trials), leading to high YI levels as represented in our 30% YI scenario.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…(2017) and Sutradhar et al. (2021): average YI of 50%–100% within a large number of practitioner field trials), leading to high YI levels as represented in our 30% YI scenario.…”
Section: Discussionmentioning
confidence: 63%
“…However, the yield response will depend on the management intensity before the biochar amendment. Consequently, when planned reasonably, realizing a biochar program on scarcely managed cropland would include charging the biochar with additional or previously unused organic fertilizers (such as cow urine, Schmidt et al (2017) and Sutradhar et al (2021): average YI of 50%-100% within a large number of practitioner field trials), leading to high YI levels as represented in our 30% YI scenario.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The modification in biochar based fertilizer with polylactic acid has demonstrated 70% crop production efficiency over conventional nitrogen fertilizers that have 30-40 % efficiency (Cen et al, 2021). The evidence from the field study indicated that a urine-enriched biochar enriched the crop production yield by 60% in rural areas of Bangladesh (Sutradhar et al, 2021). Praveen et al (2021) reported that the biochar derived from feed stocks such as coconut shell (CS), groundnut shell (GS) and rice husk (RH) costs about 0.61 USD, 0.57 USD and 0.57USD per kg, respectively.…”
Section: Socio-economic Impact and Way Forwardmentioning
confidence: 99%
“…Urine, both animal and human products, includes liquid waste that is easily accessible, inexpensive and is an organic product that contains high nutrients for plant growth (Sutradhar et al, 2021). Urine waste contains various substances needed for plant growth.…”
Section: Introductionmentioning
confidence: 99%